Insight into PET - Naylor, Helen (Cambridge University Press, 2004)
nsight into PET is a short course which prepares candidates for the PET examination. Organised paper by paper, this course combines thorough exam coverage with snappy units to give students a clear sense of progress and achievement. Supplementary activities for the classroom or self-study